Matching the Power, Voltage, and Size of Biological Systems: A nW-Scale, 0.023-mm(3) Pulsed 33-GHz Radio Transmitter Operating From a 5 kT/q-Supply Voltage - Choi, Jaebin; Aklimi, Eyal; Shi, Chen; Tsai, David; Krishnaswamy, Harish; Shepard, Kenneth L. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2015)
This paper explores the extent to which a solid-state transmitter can be miniaturized, while still using RF for wireless information transfer and working with power densities and operating voltages comparable to what could be harvested from a living system. A 3.1 nJ/bit pulsed millimeter-wave transmitter, 300 mu m by 300 mu m by 250 mu m in size, designed in 32-nm SOI CMOS, operates on an electric potential of 130 mV and 3.1 nW of dc power. Far-field data transmission at 33 GHz is achieved by supply-switching an LC-oscillator with a duty cycle of 10(-6). The time interval between pulses carries information on the amount of power harvested by the radio, supporting a data rate of similar to 1 bps. The inductor of the oscillator also acts as an electrically small (lambda/30) on-chip antenna, which, combined with millimeter-wave operation, enables the extremely small form factor.
Keywords: CMOS; ENERGY